2017
DOI: 10.1007/s11095-017-2203-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethanol on Darunavir Hepatic Clearance and Intracellular PK/PD in HIV-Infected Monocytes, and CYP3A4-Darunavir Interactions Using Inhibition and in Silico Binding Studies

Abstract: Purpose Although the prevalence of alcohol consumption is higher in HIV+ people than general public, limited information is available on how alcohol affects the metabolism and bioavailability of darunavir (DRV). Methods DRV was quantified by using LC-MS/MS method. All in vitro experiments were performed using human liver microsomes and HIV-infected monocytic cells. CYP3A4 and DRV/ Ritonavir (RTV) docking was performed using GOLD suite 5.8. Results Ethanol (20 mM) significantly decreased apparent half-life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Studies with HIV-1-infected macaques have shown increased viral load in the blood and cerebral compartments of chronic-drinking animals [8] . Moreover, previous reports from our lab suggest that ethanol reduced intracellular concentrations of antiretroviral drugs (elvitegravir, darunavir) in the HIV-1-infected U1 cell line [9] , [10] . Ethanol also increased HIV-1 replication despite the presence of elvitegravir [10] .…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Studies with HIV-1-infected macaques have shown increased viral load in the blood and cerebral compartments of chronic-drinking animals [8] . Moreover, previous reports from our lab suggest that ethanol reduced intracellular concentrations of antiretroviral drugs (elvitegravir, darunavir) in the HIV-1-infected U1 cell line [9] , [10] . Ethanol also increased HIV-1 replication despite the presence of elvitegravir [10] .…”
Section: Introductionmentioning
confidence: 55%
“…Furthermore, our laboratory has been studying the effect of alcohol consumption on antiretroviral drugs in the past few years. We have shown that the metabolism of darunavir, an important ARV drug, is influenced by ethanol, and has faster hepatic intrinsic clearance in the presence of a ritonavir-boosted darunavir combination [9] . Our previous studies have also shown that ethanol has the ability to interact with microsomal CYP3A4 and alter elvitegravir metabolism and HIV-1 replication in monocytic cells [44] .…”
Section: Discussionmentioning
confidence: 95%
“…However, the overall effects of alcohol on CYP3A4 might be complicated. Interestingly, while chronic alcohol use results in the increase of CYP3A4 expression and, thus, indirectly increases the CYP3A4 activity, alcohol itself also binds with CYP3A4 in the active site to directly affect the CYP3A4 activity [32] . The CYP3A4-alcohol binding affinity ( K d ) was determined as 5.9 mM [33] .…”
Section: Resultsmentioning
confidence: 99%
“…They reported that this alcohol-induced alteration of elvitegravir concentrations were associated with the induction of CYP3A4, and the drug transporters MRP1 and MDR1. The same group also reported the effect of alcohol on a protease inhibitor, darunavir, and its effect on hepatic clearance, intracellular pharmacokinetics, HIV suppression of darunavir in liver microsomes and U1 cells [40]. They showed that alcohol decreases apparent half-life and hepatic intrinsic clearance of darunavir when alcohol was co-exposed with a commonly used pharmaco-enhancer, ritonavir.…”
Section: Effects Of Alcohol On Art Efficacy/toxicitymentioning
confidence: 98%